Quasi-Asymptotic Behavior at the Origin of Tempered Operators - Nemzer, Dennis (Sarajevo Journal of Mathematics, 2018)
A subspace of Mikusinski operators, which was introduced by K. Yosida, is used to investigate quasi-asymptotic behavior at the origin in one dimension. As an application, an Abelian theorem of the initial type for the Stieltjes transform is established.